The Concept of Political Competence. Issue 3 (2nd October 2018) - Brinkmann, Matthias
ABSTRACT: Two crucial distinctions regarding political competence must be made. First, the mere probability that you will make a morally right decision (reliability) is distinct from your ability to skillfully make a decision (competence). Empirical and normative accounts have focused primarily on reliability, but competence is more important if we take central normative commitments seriously. Second, the competence you have on your own (direct competence) is distinct from the competence you have in contributing to some collective enterprise (contributory competence). Direct competence is likely to be extremely demanding in a democratic context, so we should move to a contributory account of competence.